A percepção docente sobre o ensino de matemática no contexto da educação escolar indígena: um estudo no Município de Belterra-Pa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
This research brings to the educational scene a discussion about the teaching conception about teaching mathematics in the context of Indigenous School Education, through a study developed in the municipality of Belterra - Pa. The research theme proposed for this work is based on the need to understand more broadly how ethnomathematics can be worked in the context of the daily life of a given village, based on the social practice of indigenous culture. The methodological procedures used to carry out this work were the bibliographical research and elements of ethnographic research, used to organize data and to describe descriptively the material culture of a given people, in this case, the indigenous peoples of Marituba village, besides the participant research that allows that the researchers interact with the members of the situations investigated. The study was carried out in the living context of villagers community community, where they participated in activities related to some social practices of the community and their interrelations with the school context. The operative referrals used were the everyday instruments of the village, besides activities with human resources, students, parents, community in general. The research results showed that teaching through ethnomathematics is a real challenge for the teacher, but it is necessary to innovate the methodological process in the teaching of mathematics, taking into account the reality of the student in the social context, valuing his learning in the community in which is inserted and leading to formal education.
Keywords: Cultura indígena; Etnomatemática; Ensino Fundamental; CNPQ:: CIÊNCIAS EXATAS E DA TERRA